(untitled) (Conferencea, 2024)
The essence of ecological education and upbringing is "Nature is our common home, it depends on me personally whether this home is healthy and perfect", "Every insect, every organism in nature has a direct impact on my life", "Nothing in nature is unlimited" not: I need to use them sparingly, because they will be needed for the people who will come to the world after me" such noble thoughts and ideas are scientifically approached in this article.